Postnatal Expansion, Maturation, and Functionality of MR1T Cells in Humans - Swarbrick, Gwendolyn M.; Gela, Anele; Cansler, Meghan E.; Null, Megan D.; Duncan, Rowan B.; Nemes, Elisa; Shey, Muki; Nsereko, Mary; Mayanja-Kizza, Harriet; Kiguli, Sarah; Koh, Jeffrey; Hanekom, Willem A.; et al. (Frontiers in Immunology, 2020)
MR1-restricted T (MR1T) cells are defined by their recognition of metabolite antigens presented by the monomorphic MHC class 1-related molecule, MR1, the most highly conserved MHC class I related molecule in mammalian species. Mucosal-associated invariant T (MAIT) cells are the predominant subset of MR1T cells expressing an invariant TCR -chain, TRAV1-2. These cells comprise a T cell subset that recognizes and mediates host immune responses to a broad array of microbial pathogens, including Mycobacterium tuberculosis. Here, we sought to characterize development of circulating human MR1T cells as defined by MR1-5-OP-RU tetramer labelling and of the TRAV1-2+ MAIT cells defined by expression of TRAV1-2 and high expression of CD26 and CD161 (TRAV1-2+CD161++CD26++ cells). We analysed postnatal expansion, maturation and functionality of peripheral blood MR1-5-OP-RU tetramer+ MR1T cells in cohorts from three different geographic settings with different tuberculosis (TB) vaccination practices, levels of exposure to and infection with M. tuberculosis. Early after birth, frequencies of MR1-5-OP-RU tetramer+ MR1T cells increased rapidly by several fold. This coincided with the transition from a predominantly CD4+ and TRAV1-2- population in neonates, to a predominantly TRAV1-2+CD161++CD26++ CD8+ population. We also observed that tetramer+ MR1T cells that expressed TNF upon mycobacterial stimulation were very low in neonates, but increased ~10-fold in the first year of life. These functional MR1T cells in all age groups were MR1-5-OP-RU tetramer+TRAV1-2+ and highly expressed CD161 and CD26, markers that appeared to signal phenotypic and functional maturation of this cell subset. This age-associated maturation was also marked by the loss of naïve T cell markers on tetramer+ TRAV1-2+ MR1T cells more rapidly than tetramer+TRAV1-2- MR1T cells and non-MR1T cells. These data suggest that neonates have infrequent populations of MR1T cells with diverse phenotypic attributes; and that exposure to the environment rapidly and preferentially expands the MR1-5-OP-RU tetramer+TRAV1-2+ population of MR1T cells, which becomes the predominant population of functional MR1T cells early during childhood.